Revolutionary Calvinist Parties in England under Elizabeth I and Charles I - Solt, Leo F. (Church history, 1958)
Some of the comparative ideas that Mr. Kingdon has dealt with in the foregoing article are elaborations of views that he suggested in his recent monograph, Geneva and the Coming of the Wars of Religion, 1555–1563. In a recent review of this book by Sir John Neale the author is praised for claiming that the “highly-organized subversive conspiracy from Geneva,” which was so important in the French wars of religion, “has a bearing on Dutch and English, not to mention Scottish, history.” What is more, Neale indicates that he “certainly finds it illuminating for an appreciation of the Puritan Classical movement in Elizabethan history.” It might be worth-while, therefore, to extend the discussion by briefly examining Mr. Kingdon's criteria for “revolutionary Calvinist parties” in connection with England in the age of Elizabeth and, later, with the period of the English civil wars of the mid-seventeenth century. Those criteria include a synodical organization, noble leadership, and a resistance theory.